2017
DOI: 10.1093/hmg/ddx118
|View full text |Cite
|
Sign up to set email alerts
|

Shortened primary cilium length and dysregulated Sonic hedgehog signaling in Niemann-Pick C1 disease

Abstract: The Niemann-Pick type C1 (NPC1) disease is a neurodegenerative lysosomal storage disorder due to mutations in the NPC1 gene, encoding a transmembrane protein related to the Sonic hedgehog (Shh) receptor, Patched, and involved in intracellular trafficking of cholesterol. We have recently found that the proliferation of cerebellar granule neuron precursors is significantly reduced in Npc1-/- mice due to the downregulation of Shh expression. This finding prompted us to analyze the formation of the primary cilium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 65 publications
4
34
0
Order By: Relevance
“…In parallel with the increased intracellular cholesterol, we found that deletion of ABCA1 can shorten the primary cilia of principal cells. This is consistent with previous studies showing that cholesterol modulates the length of cilia (Canterini et al, ; Formichi et al, ). The cilia function as a sensor of distal nephron flow (Praetorius & Spring, ) to control ATP release from the principal cells (Hovater et al, ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In parallel with the increased intracellular cholesterol, we found that deletion of ABCA1 can shorten the primary cilia of principal cells. This is consistent with previous studies showing that cholesterol modulates the length of cilia (Canterini et al, ; Formichi et al, ). The cilia function as a sensor of distal nephron flow (Praetorius & Spring, ) to control ATP release from the principal cells (Hovater et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…In parallel with the increased intracellular cholesterol, we found that deletion of ABCA1 can shorten the primary cilia of principal cells. This is consistent with previous studies showing that cholesterol modulates the length of cilia (Canterini et al, 2017;Formichi et al, 2018).…”
supporting
confidence: 94%
“…Thus, an imbalance in cholesterol homeostasis resulting from reduced NPC1 protein could have subtle effects throughout development. In support of this, abnormal expression and localization of SHH and its receptor Patched has been shown in the cerebellum of Npc1 mutant mice at P14 as well as in NPC1 patient-derived fibroblasts [63,64]. These data along with other studies highlighting the importance of cholesterol for SHH function in the developing cerebellum suggest that important connections may exist between NPC1 and SHH signaling pathways [58,65,66].…”
Section: Discussionsupporting
confidence: 60%
“…5A). Recent studies suggest that elevated intracellular Cho can shorten the primary cilium [40,41]. Since it is known that the primary cilia control the release of ATP [42] and that ATP strongly inhibits ENaC [43,44], it would be interesting to explore whether Cho can also alter ENaC activity by modulating the length of cilia.…”
Section: Discussionmentioning
confidence: 99%